E-cadherin and ZEB2 modulate trophoblast cell differentiation during placental development in pigs. Issue 6 (December 2017) - Hong, Linjun; Han, Kun; Wu, Kejia; Liu, Ruize; Huang, Ji; Lunney, Joan K; Zhao, Shuhong; Yu, Mei
Abstract : It is one of the important events that trophoblast cells within the placental folds differentiate into two types that differ in cell shape during placental development in pigs. This study showed that all the trophoblast cells were of similar shape between Yorkshire and Chinese Meishan pigs on day 26 of gestation; thereafter, the trophoblast cells located at the top of the placental folds became high columnar, while those cells at the base of the placental folds were cuboidal on day 50 of gestation. Additionally, on day 95 of gestation, all the trophoblast cells in Meishan pigs became cuboidal, but the trophoblast cells located at the top of the placental folds in Yorkshire pigs still remained columnar. The membranous E-cadherin and β-catenin were strongly co-expressed by the high columnar trophoblast cells but very weakly expressed by those cuboidal cells. Consistently, the expression pattern of ZEB2, the E-cadherin repressor, was inversely correlated with that of E-cadherin in the two types of trophoblast cells in the two breeds. Furthermore, electrophoretic mobility shift assays demonstrated the binding of ZEB2 to the E-cadherin promoter in nuclear extracts from porcine placental tissue. These findings suggest a ZEB2-dependent mechanism of trophoblast cell differentiation during placental development in pigs.